THE POTENTIAL OF FOREST BUFFER TO PREVENT STREAM FROM WATER POLLUTANTS:A CASE STUDY IN GROJOKAN SEWU SUB-WATERSHED, KARANGANYAR DISTRICT, CENTRAL JAVA - Wahyuningrum, Nining; Pramono, Irfan Budi (Secretariat of Forestry Research and Development Agency, 2013)
Population growth leads to water scarcity in terms of both quality and quantity. Agricultural and urban watersheds potentially produce more pollutantsthan forested area. It is considered that forested area has potential in storing and protecting water supply in such a way that water distribution and quality can be guaranteed. The objective ofÂ the study was to determine the relationship between the percentages of forested area in a watershed with the water quality. Thestudy was conducted in 2010in GrojokanSewu Sub-watershed, Karanganyar District, Central Java. Using GIS (Geographic Information System), this sub-watershedwas divided into four sub-sub-watershedswith different percentages of forested areas. Water samples were collected in each sub-sub-watershedto find out the relationship between the forested area and the total dissolvedsolids, turbidity, sodium, nitrite, nitrate, sulfate and organic matters. The statistical analysis indicates relationships in quadratic form between sodium, nitrite, TDS, sulfate and organic matters with the percentage ofÂ forested area (R2=0.99, R2=0.99, R2=0.98, R2=0.95 and R2=0.77, respectively). The relationships are different from those of turbidity and nitrate that have low R2 (R2=0.28 and R2=0.36) values. It implies that the forested area is capable to reduce sodium, nitrite, TDS, sulfate and organic matters, and thus water pollutants can be reduced by forest formation as it can filter water through retention of sediments and nutrients.